Farmer Househoald Strategy in Facing Price Increases to Maintain Economic Resilience in Sambit Distric of Ponorogo Regency - Ajeng Khoirotul Layly; Said Abadi (Niqosiya: Journal of Economics and Business Research, 2026)
Introduction: This research is motivated by the phenomenon of rising agricultural prices, which is one of the challenges faced by farming households in maintaining family economic stability. This condition requires households to be able to implement appropriate economic strategies. This is similar to what is experienced by farming households in Sambit District, Ponorogo, so strategies are needed to maintain the sustainability of the household economy. The research aims to analyze the economic strategies used by farming households in dealing with price increases, to analyze the reasons why farming households in Sambit District, Ponorogo, tend to store their harvests as a strategy to deal with price increases, and to analyze the impact of economic strategies on resilience to price increases. Methods: The study employed a qualitative approach with fieldwork in Sambit District, Ponorogo. Data were collected through in-depth interviews, observation, and documentation of farming households in Sambit District, Ponorogo. Data analysis was conducted through data reduction, data presentation, and conclusion drawing using Frank Ellis's livelihood strategy theory, which emphasizes income diversification, household asset management, and economic risk management strategies from an Islamic economic perspective. The research results: show that farming households use more work to store their harvests and diversify their income. Harvests are stored to maintain food availability, save money for emergencies, and wait for more favorable prices. This strategy contributes to income stability and the sustainability of household consumption. This strategy aligns with the principles of maslahah (maslahah) , the prohibition of israf (israf), and hifz al-mal ( the need for wealth) from an Islamic economic perspective.